Gamification of health classes: A quasi-experimental study of the diabetes monopoly game to enhance children’s fruit and vegetable interest - Arief Andriyanto; Ima Rahmawati; Emyk Windartik; Enny Virda Yuniarti; Ana Zakiyah; Siti Hidayatul Badriyah (Journal of Public Health and Development, 2026)
Low fruit and vegetable intake among school-aged children poses risks to health and development, often influenced by family habits and limited nutrition education. The Diabetes Monopoly (DIABETAMON) card game was developed as an engaging educational tool to promote balanced nutrition, emphasize the benefits of fruits and vegetables, and raise awareness of the consequences of unhealthy eating in a fun, child-friendly format. The objective of this study was to determine the effect of the DIABETAMON game on the interest in fruit and vegetable consumption among school-age children. A quasi-experimental design was employed, with school-aged children selected through purposive sampling and assigned to an intervention group (n = 47) and a control group (n = 52). Data were collected using a questionnaire, and statistical analysis was performed with a paired-sample t-test (α < 0.05). The results indicated that the intervention group showed a significant increase in interest in consuming fruits and vegetables (p = 0.001), whereas the control group showed no significant change (p = 0.085). The education provided incorporates elements of learning and play, which enhance interest among school-aged children and facilitate faster absorption of information emphasizing the importance of fruit and vegetable consumption. Promotive and preventive initiatives can be implemented within health services, particularly through the School Health Services (SHS). For example, increasing the provision of interactive and engaging health education games can help promote fruit and vegetable consumption among school-aged children.